Youtubers bilíngues: artefatos interculturais no cenário escolar da educação de surdos - Sanderson, Helenne Schroeder (2020)
The study entitled “Bilingual Youtubers: intercultural artifacts in the school scenario of deaf education” was developed along with the Graduate Program in Education, in the area of Special education, Inclusion and Difference. My intention in this paper was to look at intercultural, hybrid and contemporary experiences of life that, today, organize both deaf schools and movements. Thus, the problem that guided this study was to understand how content produced by bilingual youtubers has been constructing other ways to spread and consume culture in deaf school. To solve this problem, two specific objectives were proposed: (i) to identify what kinds of cultural contents in Libras are produced in the youtubers’ channels; and (ii) to understand how hearing and deaf teachers and students have been consuming youtubers’ productions at school. This study follows the theoretical-methodological perspective of cultural studies in education and deaf studies. Therefore, the paper acknowledges these fields as possibilities of analysis, as they make and effort to look at matters of the deaf universe and culture in a more plural and less generalized way. Regarding this study’s methodological organization, we assembled two sets of data: (a) five Brazilian bilingual youtubers’ channels and their contents; and (b) teachers’, hearers’ and deaf students’ narratives from a deaf school in Rio Grande do Sul. The material from these narratives were essential to understand how deaf students and teachers (hearing and deaf) consume bilingual youtubers’ content in their classes, as well as to identify the effects of the contents prepared by these channels in the school’s everyday life. By problematizing the contemporary way of life of deaf people, through an analysis of YouTube channels, I find possibilities to conceptualize the deaf school as one of the loci for transformation, negotiation and production of other forms of deaf existence, based on intercultural relations.